Field, Sandra Leonie (2020). Potentia: Hobbes and Spinoza on Power and Popular Politics - Aurelio Sainz Pezonaga (Universitat Autònoma de Barcelona. Departament de Filosofia, 2021)
Field, Sandra Leonie (2020) Potentia: Hobbes and Spinoza on Power and Popular Politics Nueva York: Oxford University Press, 320 p. ISBN 9780197528242